Engaging learners' out-of-class learning via OoCLI / Norhaslinda Hassan and Ainol Madziah Zubairi - Hassan, Norhaslinda; Zubairi, Ainol Madziah (Universiti Teknologi MARA, Pulau Pinang, 2022)
Successful language learning development is associated with active engagement in out-of-class learning activities. Against this background, the present study proposed Out-of-Class Learning Inventory (OoCLI) to assist teachers in engaging students' out-of-class language learning activities. A total of 65 students responded to the 6-point Likert scale survey and the validity and reliability of the items were analyzed using the Rasch Measurement Model; Rating Scale Model. The results showed that students learn English informally outside of the class. In particular, they have the tendency to use authentic or real-life situations when learning English outside of the class like discussing with friends and using technology as a tool to learn English.